Determinants of statutory tax rate changes by the Canadian provinces - Ferede, Ergete (My University, 2015)
Tax rate changes are some of the most significant and far-reaching decisions a government can take. In this paper we investigate the various fiscal and political factors that influence a government's statutory tax rate change choices. We employ a multinomial logit model to empirically investigate the likelihood of changes to personal income tax, corporate income tax, and provincial sales tax rates by Canadian provincial governments over the period 1973-2010. Our results indicate that provincial governments that start with higher tax rates are more likely to cut, and less likely to raise, their tax rates. Another important implication of our results is that ideology matters-provinces with left-leaning governments are less likely to cut and more likely to raise their tax rates. The results are robust to various sensitivity checks.
Keywords: optimal taxation; tax reform; tax competition; fiscal federalism